A low temperature water-cooled radiation calorimeter for estimation of concentrated solar irradiance. (June 2018) - Verma, Ram Niwas; Kumar, Rajesh; Dixit, Ambesh; Chandra, Laltu
Graphical abstract: Highlights: Radiation calorimeter is an essential device for estimation of concentrated solar irradiance. Detailed ray-based design of a newly proposed cavity-type device is presented. The devices works at a low-temperature up to 100 °C and thus benefits from the same. The device is evaluated up to 800 Suns and its capability extended up to 1000 Suns. Abstract: Radiation calorimeter is a device for assessment of the incident local concentrated solar irradiance (CSI) onto a receiver surface. This is required to evaluate the performance of a concentrated solar thermal system using, for instance a volumetric receiver, for applications. In this paper a low-temperature water cooled radiation calorimeter (RADCAL) is presented. This is designed as a cavity based on the concept of blackbody to maximize the absorption of the incident CSI on its absorber surfaces. Solar selective coatings are deposited on its reflector and absorber surface to achieve the same and are characterized using standard methodologies. This depicts an absorptivity of 0.95 and a reflectivity of 0.87 in the desired range of the solar spectrum and is theoretically verified. The absorption of energy results in temperature rise of RADCAL, which is controlled by an external water jacket to limit its value at 100 °C for mitigating the use of pressurized water. At any instant and eventually at the steady-state the CSI is estimated following the conservation of energy principle. The developed RADCAL is experimentally evaluated up to a CSI of 800 Suns (1 Sun = 1 kW/m 2 ) using Joule heating. The entire heat transfer process is analysed with the developed unsteady state one-dimensional mathematical model. A comparative assessment of the measured and calculated RADCAL body temperature provides the underlying uncertainty and confirms its design basis. Furthermore, the design and given consideration allows its use in arid desert condition with dust and wind. Thus, RADCAL is likely to serve in future for evaluating concentrated solar thermal system in arid deserts.